Efficacy of intravenous immunoglobulin treatment in immunocompromised children with H1N1 influenza: a clinical observation. (16th October 2014) - Gokturk, Bahar; Pekcan, Sevgi; Guner, Sukru Nail; Artac, Hasibe; Keles, Sevgi; Kirac, Mine; Reisli, Ismail
Abstract: Background and Aims: The appropriate treatment of pandemic H1N1 influenza which was first identified in April 2009 in Mexico is insufficient especially for immunocompromised patients. We aimed to evaluate the features and prognostic factors of the children with H1N1, especially immunocompromised ones, and whether intravenous immunoglobulin G (IVIG) replacement could aid for a better outcome. Methods: Twenty‐one hospitalized children with laboratory‐confirmed H1N1 were evaluated retrospectively. Data were extracted from files and electronic medical records. Results: The median age was 37 (1–216) months; 62% of them were under 5 years of age and 71.4% had one or more underlying disorders. Main symptoms were high fever, cough, fatigue and vomiting. Lower respiratory tract manifestations were seen in 66.6% of children. Mortality rate was 4.7%. The patient who died had the lowest lymphocyte (100/mm 3 ), thrombocyte (21 000/mm 3 ) and highest blood urea nitrogen (87 mg/dL) levels. Fifty‐eight percent of evaluated patients had one of the primary immunodeficiency disorders. Surprisingly, none of the six patients with primary immunodeficiency who are on regular IVIG replacement needed intensive care unit and died. Although median durations of cough, fever and hospitalization were lower, they did not change statistically according to get IVIG replacement regularly ( P = 0.47, 0.97, 0.09, respectively). Conclusion: Our study is important while it is the first one that shows the course of primary immunodeficient children with H1N1 infection who were on regular IVIG replacement. A trial of high‐dose IVIG may be a useful adjunctive therapy in severe H1N1 influenza, particularly in the immunocompromised patients.